An experimental and numerical investigation of particles fluid dynamic flow and energy transfer in a heat exchanger. Part 1. An experimental and numerical granular material flowability study - Cieslakiewicz, Waldemar; Khumalo, Samkelo; Madyira, Daniel; Scholtz, Dewald; Sterfontein, Jan (Technical Sciences, 2025)
Flowability is of great importance to a lot of processes especially granular material handling and heat transfer. In the industry achieving the highest heating efficiency of granular material heat exchanger is the most important factor. Heating/cooling area size is one of the critical factors in heat transfer processes and is highly dependent on flowability. The complexity of optimizing flowability can only be solved in two ways, either through experiment or computational modelling. However, the simulation technique is more time efficient and cost effective compared to the experimental analysis technique. Nonetheless, the CFD methodology requires prior validation of the model with the experiment. This study comprises of the experimental and numerical analysis of granular material flowability, and it aims at establishing a balanced flow of spherical silicon particles in a heat exchanger and developing a validated model that can be used for design optimisation. A Discrete Element Method (DEM) is employed in Simcenter STAR CCM+ to analyse the flow behaviour and is validated qualitatively and quantitatively from the experimental data. The results from both the simulation and the experiment exhibit a similar trend, indicating consistency between the two approaches. In both cases, the particle velocities are not uniform within the heat exchanger, as variations are observed across different regions, from 2 mm/s to 9 mm/s. Specifically, particles near the heat exchanger walls experience lower velocities due to higher frictional resistance, while those in the central flow stream, especially close to the outlet, move at relatively higher speeds. Quantitatively, the percentage difference between the simulation and experimental results is 9.53% for particle velocity and 5.61% for mass flow rate, which falls within an acceptable range for computational modelling of granular flow. This level of accuracy indicates that the simulation effectively captures the key flow dynamics within the heat exchanger, making it a reliable tool for further analysis. The study shows convincingly that the model was validated successfully, however investigated heat exchanger is highly inefficient but using the validated model can be optimized. The study comprises two parts. The first one presents the experimental and numerical particles flow analysis of the fluid (granular material), while the second one focuses on the experimental and numerical energy transfer (heating/cooling) analysis.